English Teachers' Views on the Use of Web 2.0 Tools in Educational Environments - ARABACI, Imam Bakir; AKILLI, Ceyda (Asian Journal of Education and Training, 2021)
New practices that support the use of technology in education are developed in order to create a modern education-training process within the framework of quality and efficiency standards throughout the world. Web 2.0 tools that help to make the most of technology in educational environments are one of these applications. It has been proven that Web 2.0 tools, which were used in education in Turkey in 2009, increase the motivation of students and increase their academic success. Teachers' professional development accelerates by producing new materials with these tools, and cooperation, communication and coordination among colleagues increase. The aim of the study is to reveal the opinions of English teachers working in Elazig about the use of Web 2.0 tools in educational environments. The study is based on the situation analysis technique, which is one of the qualitative research methods. The interview form developed by the researchers was used as the data collection tool. The working group consists of 30 English teachers working in Elazig province of Turkey. The responses of the participants to the questions in the interview form were subjected to content analysis, categories were created, and frequencies and percentages were determined. According to the results of the research, teachers generally have positive perceptions of Web 2.0 tools, they generally use these tools for content development, Web 2.0 tools provide positive contributions to classroom management and student development.